DESKRIPSI SOSIAL MASYARAKAT TERHADAP GAMBAR DAN TULISAN YANG TERDAPAT DALAM GEROBAK TRUK - Asih Prihandini; Ahmad Fauzan (Al-Tsaqafa : Jurnal Ilmiah Peradaban Islam, 2018)
ABSTRACTThis journal discusses the description of the lives of truck drivers represented in image and text message on the back of the truck. The image and text message become interesting since some readers feel it as a mere entertainment. However, to see the interpretation is through the perspective of linguistics. The theory of semiotics used analyze the point of view and meaning of images and writings that are represented.  By using the connotation and denotation meaning contained in semiotics, the language used is analyzed. The method used in this research is qualitative to describe the statement or the existing picture. The purpose of this study is to get understanding about image and text message illustrated on the back of the truck. The conclusion is that every writing and illustration illustrated in the truck has its own purpose which leads to the attention and criticism of the society towards the development of the era so that the meaning becomes part of the representation of some people who live on the streets.Keywords : image; text message;  truck; connotation; denotation